(Calamansi) Citrofortunella Microcarpa Rind Extract As Plant Derived Green Corrosion Inhibitor For Mild Steel In 1.0M Hcl. Issue 1 (April 2020) - Arguelles, Gian Carlo E.; Torres, Mark Ceazar D.; Wu, Brian James U.; Olay, Jerry G.; Ong, Renato C.
Abstract: The inhibitive action of extracts from Citrofortunella microcarpa (Calamansi) peels on mild steel in 1.0M HCl solution has been studied using the weight-loss method, electrochemical method, and SEM-EDX analysis. The measurements showed that calamansi peels have good inhibition properties. Weight loss results suggest that inhibitive efficiency increases as the concentration increases. It was also found that the adsorption stabilizes at 72 hours and degrades at longer immersion times. SEM studies of the immersed mild steel showed the decreasing extent of corrosion attack on mild steel at an increasing ratio of inhibitor, while EDX analysis shows the reduction of the formation of corrosion products, suggesting the formation of inhibitor film on the mild steel surface. The Calamansi peel extract inhibitor obeys the Langmuir adsorption isotherm model and the mode of adsorption was found to be physical and spontaneous. The results of the electrolysis technique have shown the favoring of inhibition in cathodic reactions.